KEPEMIMPINAN DALAM PANDANGAN FILSUF ARAB (Studi Kitab Muqaddimah Karya Ibnu Khaldun) - Inayatul Mas'adah (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2021)
One of the great Muslim philosophers whose name is still considered to this day is Ibn Khaldun. Many important ideas of his thinking are contained in his work Muqaddimah, one of which is about leadership. His fairly mature experience in the world of practical politics made him have a mature understanding of the concept. In this article, Ibn Khaldun's thoughts on leadership will be reviewed. From the analysis that the author did, this study obtained the result that according to Ibn Ibn Khaldun leadership is something that must exist and in accordance with the teachings of Islam. According to him, leadership can be achieved through the existence of supremacy achieved with fanaticism through asabiyyah. In addition to asabiyyah, religion also plays a role in the establishment of leadership. In fact, the solidarity produced by religion is much stronger than that produced only by asabiyyah. In addition, Ibn Khaldun also gave some criteria for a leader, including having knowledge, being able to do justice, competent, physically and spiritually healthy, and having a lineage from the tribe of Quraish.